FAKTOR INDIVIDU YANG MEMPENGARUHI PERSEPSI PETANI TERHADAP SISTEM USAHATANINYA PADA LAHAN REHABILITASI TN MERU BETIRI (Individual factors influencing perception of farmer on its farming system at rehabilitation land of TN Meru Betiri) - C Yudi Lastiantoro (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2020)
ABSTRACTThe individual factors of farmers who manage the rehabilitation land in Meru Betiri National Park (TN Meru Betiri) have relationships with the perceptions of their arable land and the surrounding forest areas. The purpose of this study was to determine individual factors of farmers influencing their perceptions on forest areas which should not be disturbed, stateowned forest areas, existing forest parts of TN Meru Betiri, forests as sources of building materials, forests as sources of animal feed, rehabilitation land as a livelihood, rehabilitation land as a food source, and rehabilitation land as the main cultivable land. The study was conducted in 2017, in Wonoasri Village, Tempurejo District, Jember Regency, East Java. The research methodology uses quantitative descriptive analysis. The study showed that farmers’ perception on rehabilitation land management toward forest areas and TN Meru Betiri rehabilitation area at a good level, they realized that  the existence of the rehabilitation land and its surrounding forest  is the forests area of TN Meru Betiri. Individual factors, namely the level of education has a significant effect to the perceptions of the reabilitation land of TN Meru as a food source. The level of income has a  significant influence on  the perception of forests as a source of animal feed and rehabilitation land as a livelihood.  The implication of the finding is that it is difficult for Meru Betiri National Park to request the rehabilitation land from the managing farmers to be used as forest area.Keywords: individual factors; perception; rehabilitation land; Meru Betiri National Park ABSTRAKFaktor individu petani pengelola lahan rehabilitasi  Taman Nasional (TN) Meru Betiri mempunyai hubungan terhadap persepsi mereka  pada lahan garapannya  dan  Kawasan hutan di sekelilingnya. Tujuan penelitian ini untuk mengetahui faktor individu petani yang mempengaruhi persepsinya terhadap 1) kawasan hutan untuk tidak diganggu, 2) Kawasan hutan milik negara, 3) hutan yang ada milik TN Meru Betiri, 4) hutan sebagai sumber bahan bangunan, 5) hutan sebagai sumber pakan ternak, 6) lahan rehabilitasi sebagai mata pencaharian, 7) lahan rehabilitasi sebagai sumber pangan, 8) lahan rehabilitasi sebagai garapan utama. Penelitian dilaksanakan pada tahun 2017, di Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember Jawa Timur. Metodologi penelitian menggunakan deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa persepsi petani pengelola lahan rehabilitasi terhadap kawasan hutan dan lahan rehabilitasi TN Meru Betiri pada tingkat baik, artinya mereka mengakui keberadaan lahan rehabilitasi dan hutan di sekelilingnya merupakan kawasan hutan TN Meru Betiri. Faktor individu, yaitu tingkat pendidikan mempunyai hubungan yang signifikan terhadap persepsi lahan rehabilitasi TN Meru Betiri sebagai sumber pangan. Tingkat pendapatan mempunyai pengaruh yang   signifikan terhadap persepsi hutan sebagai sumber pakan ternak dan lahan rehabilitasi sebagai matapencaharian. Implikasi dari temuan tersebut adalah pihak TN Meru Betiri  sulit untuk meminta kembali lahan rehabilitasi dari petani pengelolanya untuk dijadikan Kawasan hutan.Kata kunci: faktor individu; persepsi; lahan rehabilitasi; Taman Nasional Meru Betiri